13.4k views
2 votes
HdshdgdbbebzbdvxgsjjfbJJnzBBSbdbdbdbdbdbdbd help me plzzzz

HdshdgdbbebzbdvxgsjjfbJJnzBBSbdbdbdbdbdbdbd help me plzzzz-example-1

1 Answer

5 votes

[Note: you can only combine exponents when the base is the same.

x³ "x" is where the base is

For example:

x²(y³) = x²y³



When you multiply a variable/number with an exponent by a number with an exponent, you add the exponents together.

For example:


(x^(2) )(x^(4))=x^(2+4)=x^6


(x^(2))(x^6)=x^(2+6)=x^8


(2^4)(2^1)=2^(4+1)=2^5


When an exponent is negative, you move the number and the exponent to the other side of the fraction to make the exponent positive.

For example:


x^(-2) or
(x^(-2))/(1)=(1)/(x^2)


(1)/(y^(-3)) =(y^3)/(1) or y³





A.)
3^(-4)(3^(-3))=3^(-4+(-3))=3^(-4-3)=3^(-7)=(1)/(3^7)

B.)
3^(-5)(3^2)=3^(-5+2)=3^(-3)=(1)/(3^3)

C.)
3^6(3)=3^(6+1)=3^7

D.)
3^5(3^(-12))=3^(5+(-12))=3^(-7)=(1)/(3^7)

E.)
3^(-7)(3^1)=3^(-7+1)=3^(-6)=(1)/(3^6)

F.)
3^2(3^(-9)) = 3^(2+(-9))=3^(-7)=(1)/(3^7)


Your answer is A, D, F

User Martin Freedman
by
6.0k points